Educational Reforms in Religious Seminaries (Madaris) in Pakistan - Nawaz, Muhammad; Mahmood, Naseem; Aleem, Abdul (Al-Irfan, 2021)
It is undeniable reality that Islam emphasis the significance of education as the first verse that descended on the Holy Prophet Muhammad (ﷺ) provided great impetus for the human pursuit of knowledge. It concludes that there is no distinction between religious education and any other kind of education as knowledge contains both religious and worldly education. The Holy Quran urges the mankind to think, ponder and acquire knowledge. The educational institutions were focusing on imparting both religious and contemporary education from the early era of Islam to medieval times. Consequently, the Islamic Seminaries had produced not only the religious scholars but also brilliant professionals, authorities and virtuous citizens. Unfortunately, with the passage of time the gap between Islamic Seminaries and government school systems was expanded. The basic aim of this research is to explore the efforts, strategies devised through promulgated various ordinances, rules and regulations at state level to integrate religious Islamic Seminaries (Madaris) with mainstream education system, and to introduce reforms and transformations in their courses and teaching methodology to enabling these Islamic Seminaries to play their vital role of producing not only religious scholars but also leaders in all fields of learning and human endeavor. This study is also an effort to highlight the background of Islamic Seminaries and their curricula in various periods especially the period after 9/11 attacks which demanded tangible reforms and transformation in the curricula of the Islamic Seminaries to cater the contemporary needs for preparing a morally trained generation with a special association with religion that will play the role of advocates of Islam throughout the world. Results, recommendations have been mentioned at the end of the study.